SISTEM INFORMASI JASA PENGIRIMAN BARANG BERBASIS WEBSITE DI KABUPATEN WONOSOBO - Khafik Rozak; Muslim Hidayat; Asnawi, Muhamad Fuat; Nur Hasanah; Nulngafan (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2024)
Small and Medium Enterprises (SMEs) in the villages of Wonosobo are the backbone of the local economy, but they face significant challenges such as market accessibility, infrastructure, and limited human resources. One of the main obstacles is the difficulty in shipping goods, with reliance on local motorcycle taxis that are not always available and have limited capacity, leading to increased costs and delays. This challenge is globally relevant with the rise of electronic commerce and the demand for fast delivery. Understanding the local difficulties in shipping goods is key to designing the right solutions. The author proposes developing a web-based shipping information system in Wonosobo Regency, utilizing Village-Owned Enterprises (BUMDes) in each village as agents. Data collection methods include observation, interviews, and literature study. The development method used is the Waterfall method, with alpha and beta testing to ensure system reliability and usability before market launch. This system aims to enhance the efficiency and effectiveness of goods delivery through digitalization.